Analisis Prevalensi Dan Faktor-Faktor Risiko Melahirkan Anak Stunting Pada Ibu Hamil di Desa Bumi Agung, Kecamatan Bumi Agung, Kabupaten Way Kanan - Wawan Abdullah Setiawan; Paul Benyamin Timotiwu; Muhammad Iqbal; Ramadhan Triyandi (BULLET : Jurnal Multidisiplin Ilmu, 2026)
Stunting has become a serious public health problem, including in rural areas. This study aims to analyze the risk factors that potentially cause stunting in Bumi Agung Village, Bumi Agung Sub-district, Way Kanan Regency, and propose targeted solutions. This research used a qualitative descriptive method through field observations and in-depth interviews (case study) with a pregnant woman identified as at-risk, as well as an analysis of local posyandu data. The results showed that although the general prevalence of stunting cases in the village from mid-2023 to early 2024 was controlled, there were still pregnant women with Mid-Upper Arm Circumference (MUAC) below the standard. The main factors causing pregnant women to be at risk of giving birth to stunted children in this case were not a lack of nutritional knowledge or access to health services, but rather a high burden of physical activity (heavy household chores) and mental stress experienced by the mother during pregnancy. Suggested solutions include education involving the family (especially husbands) to support the physical and psychological condition of pregnant women, improvement of supporting infrastructure, and cross-sectoral collaboration in monitoring pregnant women's nutrition.